2018
DOI: 10.1186/s12939-018-0806-0
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of safety and quality standards for private health care providers: a case-study from the Republic of Srpska, Bosnia and Herzegovina

Abstract: BackgroundRegulation of private health care providers (PHPs) in middle-income countries can be challenging. Mandatory safety and quality standards for PHPs have been in place in the Republic of Srpska since 2012, but not all PHPs have adopted them yet. Adoption rates have differed among different types of providers. We studied three predominant types of PHPs to determine why the rate of adoption of the standards varies among them.MethodsThis study used a mixed methods approach, which allowed the integration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 32 publications
(29 reference statements)
0
8
0
1
Order By: Relevance
“…The seventh paper, a study by Rakic et al [ 19 ] on Bosnia-Herzegovina, sheds light on some of the challenges entailed in regulating NSPs in a setting characterized by limited government enforcement capacity. They describe a mechanism designed to certify provider compliance with mandatory safety and quality standards, which has been in place since 2012, and examine why providers do or do not adopt.…”
Section: Resultsmentioning
confidence: 99%
“…The seventh paper, a study by Rakic et al [ 19 ] on Bosnia-Herzegovina, sheds light on some of the challenges entailed in regulating NSPs in a setting characterized by limited government enforcement capacity. They describe a mechanism designed to certify provider compliance with mandatory safety and quality standards, which has been in place since 2012, and examine why providers do or do not adopt.…”
Section: Resultsmentioning
confidence: 99%
“…Bosnia and Herzegovina presents a country at the relatively high end of the universal coverage spectrum [ 17 ]. The country has widespread coverage of health services and relies on NSPs, who are engaged through the national social health insurance program.…”
Section: Resultsmentioning
confidence: 99%
“…Ensuring that NSPs comply with quality standards requires government involvement. In Bosnia & Herzegovina, a certification regulation was introduced in 2009 by the Ministry of Health and Social Welfare to improve safety, trust, and quality [ 17 ]. An independent agency for certification was created in 2012 to assess provider’s compliance with this regulation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these studies did not explore and describe impact at the clinic level in detail. At the same time, studies have found that professionals from general practice are concerned about the administrative burdens of accreditation [12, 13], concerns which have also been raised by health professionals in other health care settings [1]. Hence, when investigating the impact of accreditation, it is important to pay attention to positive as well as negative experiences.…”
Section: Introductionmentioning
confidence: 99%